2014
DOI: 10.1590/0104-6632.20140312s00002668
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of carrot (Daucus carota) drying in microwave and in vacuum microwave

Abstract: -Drying is a single operation employed to prolong the life of a large quantity of vegetables. Carrot (Daucus carota) drying has been the subject of many studies. This plant has been highlighted in the human diet for having high nutritional value, mainly due to the high content of β-carotene. In this work, carrot drying behavior was studied in a regular microwave dryer and a vacuum microwave dryer. A vacuum of 450 mmHg was applied for drying of carrot in different geometrical shapes (cubes, discs and sticks). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…The same interpretation is possible to be done with the fitness of Page's equation (Table ) with respect to the parameter k , which represents the drying rate could represent well the evolution of moisture content and is largely employed for describing the drying behavior of fruits and vegetables (Béttega, Rosa, Corrêa, & Freire, ; Perea‐Flores et al, ). However, the fitness of Page's equation was better than those obtained with Fick's model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same interpretation is possible to be done with the fitness of Page's equation (Table ) with respect to the parameter k , which represents the drying rate could represent well the evolution of moisture content and is largely employed for describing the drying behavior of fruits and vegetables (Béttega, Rosa, Corrêa, & Freire, ; Perea‐Flores et al, ). However, the fitness of Page's equation was better than those obtained with Fick's model.…”
Section: Resultsmentioning
confidence: 99%
“…The convective experiments presented lower shrinkage, as consequence, higher rehydration capacity. These features can be advantageous because the product with higher porosity can be rehydrated more easily (Béttega et al, ). The microwave–convective drying presented intermediated values of CR, it is well known that intercellular gaps created by microwave energy could absorb water during rehydration (Corrêa et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The average drying rates during the period with a constant drying rate and the initial and final moisture content of cranberries during that period are presented in Table 4. Many researchers investigating the kinetics of microwave-vacuum drying of fruit, vegetables and mushrooms have reported only the long phase with a decreasing drying rate, accompanied by a very short F-frozen cranberries; FM1-frozen cranberries subjected to microwave vacuum pretreatment at microwave power of 100 W; FM5-frozen cranberries subjected to microwave vacuum pretreatment at microwave power of 500 W; FM8-frozen cranberries subjected to microwave vacuum pretreatment at microwave power of 800 W MR-moisture loss ratio; SR-solids gain ratio F-frozen cranberries; FM1-frozen cranberries subjected to microwave vacuum pretreatment at microwave power of 100 W; FM5-frozen cranberries subjected to microwave vacuum pretreatment at microwave power of 500 W; FM8-frozen cranberries subjected to microwave vacuum pretreatment at microwave power of 800 W phase or the absence of a phase with a constant drying rate (Zielinska and Michalska 2016;Béttega et al 2014;Dak and Pareek 2014;Giri and Prasad 2007). In contrast, Bondaruk et al (2007) reported a relatively long phase with a constant drying rate during microwave-vacuum drying of potatoes, which is consistent with our results.…”
Section: The Effect Of Initial Pretreatment On the Kinetics Of Microwmentioning
confidence: 99%
“…AD in nonstationary phase also reduced the unfavorable effects in β-carotene, color changes, decay, and degradation phenomenon (Kowalski, Szadzinska, & Lechtanska, 2013), hot-air drying also appreciably decreases immobile water in microstructures of dried carrots. Drying of carrot slices through VMD technique showed rehydration ability, ascorbic acid content, β-carotene, and softer texture compared to freeze andAD (Bettega, Rosa, Correa, & Freire, 2014). Similarly, the recent advanced technique like "ultrasound assisted vacuum drying" has been applied to carrot slices.…”
Section: Carrotsmentioning
confidence: 99%